The Cooperation Pattern between the Maluku Provincial Government and the Private Sector in the Arrangement and Normalization of Ex-Illegal Gold Mining Allegedly Prone to Corruption - Arman Anwar; Irma Halima Hanafi; Muhammad Irham (Integritas: Jurnal Antikorupsi, 2021)
Buru District has been developed since 1970 as a transmigration area. The nuance of agriculture is characteristic of Buru Regency so that it is designated as a national rice granary area. However, since gold was discovered in Mount Botak and Gogrea in 2011, Buru Regency has turned into an illegal gold mining area. As a result, there is massive environmental damage and pollution caused by the use of cyanide and mercury by illegal miners. To overcome this problem, the Maluku Provincial Government is working with a third party (private) to normalize and restore the environment in ex-illegal mining, but the cooperation is prone to corruption. The purpose of this research is to prevent corruption in this sector. The research method uses Social Network Analysis, the data is qualitative. The research findings show that cooperation between the Maluku Provincial government and third parties (private) who are prone to corruption can be prevented by mapping the vulnerability of corruption to determine the pattern of relations between cooperative actors who tend to be easily bribed so that a cooperation model that does not have corruption implications can be obtained. Key words: Corruption; Mining; Cooperation; Local government; Private;